2017
DOI: 10.15252/embr.201643191
|View full text |Cite
|
Sign up to set email alerts
|

NELF ‐E is recruited to DNA double‐strand break sites to promote transcriptional repression and repair

Abstract: Double-strand breaks (DSBs) trigger rapid and transient transcription pause to prevent collisions between repair and transcription machineries at damage sites. Little is known about the mechanisms that ensure transcriptional block after DNA damage. Here, we reveal a novel role of the negative elongation factor NELF in blocking transcription activity nearby DSBs. We show that NELF-E and NELF-A are rapidly recruited to DSB sites. Furthermore, NELF-E recruitment and its repressive activity are both required for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 67 publications
3
63
0
Order By: Relevance
“…In agreement with ATM acting upstream of MST2 and regulating rDNA transcription via activating several responses (Ciccia et al , ; Larsen et al , ), we observed a more profound impact on rDNA transcription in the absence of ATM compared with MST2 deletion alone and combination of both did not have a greater impact on rDNA silencing (Fig C). Recent studies have shown involvement of DNA‐PK and PARP in Pol I and Pol II transcriptional repression in the presence of DNA damage (Pankotai et al , ; Calkins et al , ; Awwad et al , ). We therefore checked whether inhibition of DNA‐PK or PARP could affect MST2 kinase activity but did not observe any impact (Fig EV3F).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with ATM acting upstream of MST2 and regulating rDNA transcription via activating several responses (Ciccia et al , ; Larsen et al , ), we observed a more profound impact on rDNA transcription in the absence of ATM compared with MST2 deletion alone and combination of both did not have a greater impact on rDNA silencing (Fig C). Recent studies have shown involvement of DNA‐PK and PARP in Pol I and Pol II transcriptional repression in the presence of DNA damage (Pankotai et al , ; Calkins et al , ; Awwad et al , ). We therefore checked whether inhibition of DNA‐PK or PARP could affect MST2 kinase activity but did not observe any impact (Fig EV3F).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Awwad et al investigate the physiological relevance of NELF‐mediated silencing in response to DNA damage by assessing the importance of NELF‐E for DSB repair. NELF‐E knock‐down moderately increases cell sensitivity to ionizing radiation and impairs DSB repair by homologous recombination and non‐homologous end‐joining . These results suggest that NELF‐E silencing activity at DSBs may be critical to promote repair, although this still needs to be formally demonstrated.…”
Section: Model For Nelf‐mediated Transcriptional Silencing Near Dsbsmentioning
confidence: 97%
“…This first set of data suggests that NELF‐E acts locally to switch off genes close to DSBs. In line with this hypothesis, Awwad et al investigate NELF‐E recruitment to damaged DNA, using once again three complementary approaches: laser‐induced damage, I‐SceI cut, and Cas9‐mediated DSB. Thus, they establish that both NELF‐E and NELF‐A relocalize to DSBs.…”
Section: Model For Nelf‐mediated Transcriptional Silencing Near Dsbsmentioning
confidence: 99%
See 2 more Smart Citations